Penerapan terapi pernapasan bibir mengerucut (pursed lips breathing) menggunakan metode tiup balon terhadap kadar saturasi oksigen pada pasien asma - Djamaludin, Djunizar; Slivia, Andi Bunga; Keswara, Umi Romayati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Asthma is a heterogeneous disease characterized by chronic inflammation of the airways. This can affect oxygen saturation levels in asthma patients. One non-pharmacological treatment for asthma patients is the pursed-lip breathing technique with a modified inflatable balloon. The prevalence of asthma in Lampung Province is 1.6%, with 503 cases of asthma relapse in the past 12 months, ranking fourth in the relapse rate. Purpose: To determine the effect of the pursed-lip breathing technique with a modified inflatable balloon on oxygen saturation levels in asthma patients. Method: This quantitative study used a quasi-experimental design with a two-group approach. The population in this study were asthma patients at Dr. A. Dadi Tjokrodipo Regional General Hospital, Bandar Lampung, with a sample size of 30 individuals. Sampling was conducted using a total sampling technique. Data were collected using an observation sheet. Data were analyzed using an independent t-test. Results: Oxygen saturation levels in asthma patients in the intervention group were higher (94.27 ± 1.387) than in the control group (91.20 ± 1.699). There was a significant effect between the pursed-lip breathing technique and the balloon blowing modification on oxygen saturation levels in asthma patients, with a p-value of 0.000. Conclusion: There was a significant effect between the pursed-lip breathing technique and the balloon blowing modification on oxygen saturation levels in asthma patients, with a p-value of 0.000. Suggestion: Nursing staff can apply the pursed-lip breathing technique and the balloon blowing modification as an alternative therapy to increase oxygen saturation levels in asthma patients. Keywords: Asthma Patients; Balloon Blowing; Oxygen Saturation Levels; Pursed-Lip Breathing. Pendahuluan: Asma merupakan suatu penyakit yang heterogen, dimana adanya inflamasi kronis pada saluran pernapasan. Akibatnya dapat mempengaruhi kadar saturasi oksigen pada pasien asma. Salah satu penanganan nonfarmakologi yang dapat diberikan pada pasien asma antara lain teknik pursed lips breathing dengan modifikasi blowing ballon. Prevalensi asma di Provinsi Lampung 1.6% dengan prevalensi kekambuhan asma dalam 12 bulan terkhir yaitu 503 dengan urutan tingkat kekambuhan ke-4. Tujuan: Untuk mengetahui pengaruh teknik pursed lips breathing dengan modifikasi ballon blowing terhadap kadar saturasi oksigen pada pasien asma. Metode: Penelitian kuantitatif menggunakan rancangan quasi eksperimen dengan pendekatan two group. Populasi dalam penelitian ini adalah pasien asma di RSUD.DR.A.Dadi Tjokrodipo Bandar Lampung dengan jumlah sampel 30 partisipan. Pengambilan sample menggunakan teknik total sampling. Data dikumpulkan menggunakan lembar observasi. Analisa data menggunakan uji independen t-test. Hasil: Kadar saturasi oksigen pasien asma pada kelompok intervensi lebih tinggi (94.27 ± 1.387) dibandingkan kelompok kontrol (91.20 ± 1.699). Terdapat pengaruh teknik pursed lips breathing dengan modifikasi ballon blowing dengan nilai p (0.000) terhadap tingkat saturasi oksigen pada pasien asma. Simpulan : Adanya pengaruh teknik pursed lips breathing dengan modifikasi blowing ballon dengan p-value (0.000) terhadap kadar saturasi oksigen pada pasien asma. Saran: Tenaga keperawatan dapat menerapkan asuhan keperawatan teknik pursed lips breathing dengan modifikasi blowing ballon sebagai alternatif tindakan guna meningkatkan kadar saturasi oksigen pada pasien asma. Kata Kunci: Ballon Blowing; Kadar Saturasi Oksigen; Pasien Asma; Pursed Lips Breathing.